A one-dimensional modeling study on the effect of advanced insulation coatings on internal combustion engine efficiency. (July 2021) - Broatch, Alberto; Olmeda, Pablo; Margot, Xandra; Gomez-Soriano, Josep
This article presents a study of the impact on engine efficiency of the heat loss reduction due to in-cylinder coating insulation. A numerical methodology based on one-dimensional heat transfer model is developed. Since there is no analytic solution for engines, the one-dimensional model was validated with the results of a simple "equivalent" problem, and then applied to different engine boundary conditions. Later on, the analysis of the effect of different coating properties on the heat transfer using the simplified one-dimensional heat transfer model is performed. After that, the model is coupled with a complete virtual engine that includes both thermodynamic and thermal modeling. Next, the thermal flows across the cylinder parts coated with the insulation material (piston and cylinder head) are predicted and the effect of the coating on engine indicated efficiency is analyzed in detail. The results show the gain limits, in terms of engine efficiency, that may be obtained with advanced coating solutions.